Joan Rivers: Comedy and Identity on the Road to Fashion Police - (:unkn) unknown (My University, 2021)
This thesis analyzes how Joan Rivers’ comedy content and style changed during the first 30 years of her career and how these changes impacted Rivers’ presentation of her identity as a Jewish female comedian. This project focuses on Joan Rivers’ career in two sections: her early career with its reliance on a self-deprecatory style of humor spanning roughly from her first appearance on The Tonight Show in 1965 to the early 1980s, and a transitional period in her career that saw a shift toward a celebrity gossip style of humor during the 1980s. I perform textual analyses of some of Rivers’ most prominent work during the first 30 years of her career, including her work on the stand-up comedy club circuit, her comedy albums, and her time as a guest host on The Tonight Show. I also perform contextual analyses in order to situate Rivers’ comedy in specific socio-historical moments and to identify how Rivers’ comedy is connected to larger changes in American society. This thesis argues that the changes that Joan Rivers’ comedy content and style experienced during the first 30 years of her career were the product of various changes in American society, including the rise of feminism, the growing popularity of celebrity gossip, and increased competition between female comedians in a changing comedy industry.
Keywords: Celebrity; Comedy; Gender; Jewish; Joan Rivers; Stand-up